Foundations of information and knowledge systems : 7th International symposium, FoIKS 2012, Kiel, Germany, March 5-9, 2012. Proceedings - Sali, Attila; Lukasiewicz, Thomas (Lecture Notes in Computer Science, 2012)
This book constitutes the proceedings of the 7th International Symposium on Foundations of Information and Knowledge Systems, FoIKS 2012, held in Kiel, Germany, in March 2012. The 12 regular and 8 short papers, presented together with two invited talks in full paper-length, were carefully reviewed and selected from 53 submissions. The contributions cover foundational aspects of information and knowledge systems. These include the application of ideas, theories or methods from specific disciplines to information and knowledge systems, such as discrete mathematics, logic and algebra, model theory, informaiton theory, complexity theory, algorithmics and computation, statistics, and optimization.